Sharing information in the credit market: Contract-level evidence from U.S. firms - Doblas-Madrid, Antonio; Minetti, Raoul (Journal of Financial Economics, 2013)
We investigate the impact of lenders' information sharing on firms' performance in the credit market using rich contract-level data from a U.S. credit bureau. The staggered entry of lenders into the bureau offers a natural experiment to identify the effect of lenders' improved access to information. Consistent with the predictions of Padilla and Pagano, 1997, Padilla and Pagano, 2000 and Pagano and Jappelli (1993), we find that information sharing reduces contract delinquencies and defaults, especially when firms are informationally opaque. The results also reveal that information sharing does not reduce the use of guarantees, that is, it may not loosen lending standards.